Characteristics of blood pressure in pheochromocytoma - Zelinka, Tomás; Pacák, Karel; Widimský, Jirí (Annals of the New York Academy of Sciences, 2006)
Pheochromocytomas are catecholamine-producing tumors arising from chromaffin cells. One of the most typical symptoms of the catecholamine-excess state is hypertension either in the sustained or paroxysmal form, and its severity does not depend on the level of circulating catecholamines. On the other hand, hypertension in pheochromocytoma is very often characterized by the amelioration or even inversion of the circadian blood pressure rhythm. In some subjects, high circulating levels of catecholamines lead to the enhanced blood pressure variability. One possible explanation for such blood pressure variability is the desensitization of the catecholamine receptors due to high levels of circulating catecholamines.
Keywords: ambulantní monitorování krevního tlaku; nádory nadledvin; Humans; krevní tlak; lidé; Blood Pressure; Adrenal Gland Neoplasms; Blood Pressure Monitoring, Ambulatory; Pheochromocytoma; feochromocytom